Relevansi Sistem Pendidikan Pesantren Salaf di Era Modernisasi - Luluk Maktumah; Mighfar, Shokhibul (Edukais : Jurnal Pemikiran Keislaman, 2022)
Many Islamic Boarding Schools in the Modern Era have made changes by combining the formal and non-formal education systems. The problem that will be reviewed in this study is how is the education system, is the education system at this Islamic boarding school relevant to the current era of modernization? What are the superior values. Data collection techniques are carried out by means of observation, interviews, documentation. Furthermore, the analysis of the data in this study is more tinkering during the process in the field together with data collection. The results of this study, the education system at Pondok Pesantren Salafiyah Syafi'iyah Jatisono is a modern salaf education system. It is evident from the observations made that the learning system at the Salafiyah Syafi'iyah Jatisono Islamic Boarding School uses methods such as sorogan, bandongan, and deliberation/basulmasail. As well as running a relatively modern education system, namely AMSILATI (quick method of reading the yellow book)